(untitled) (Intent Research Scientific Journal, 2023)
Healthy and beautiful teeth are the most important element of a person’s attractiveness. Cosmetic issues are the focus of dental clinics. Veneers and laminates made of ceramic and composite materials have become very popular as a means of quickly changing the appearance. The rapid development of materials science in dentistry and new methods of aesthetic dentistry have made it possible to restore and correct the color, shape and position of teeth, recreate harmonious bites and smiles. Bonding systems and composite materials make it possible to eliminate aesthetic obstacles without the use of traditional orthopedic methods of treatment.